1999
DOI: 10.1021/bi983030b
|View full text |Cite
|
Sign up to set email alerts
|

A Refined Model for the Solution Structure of Oxidized Putidaredoxin,

Abstract: A refined model for the solution structure of oxidized putidaredoxin (Pdxo), a Cys4Fe2S2 ferredoxin, has been determined. A previous structure (Pochapsky et al. (1994) Biochemistry 33, 6424-6432; PDB entry ) was calculated using the results of homonuclear two-dimensional NMR experiments. New data has made it possible to calculate a refinement of the original Pdxo solution structure. First, essentially complete assignments for diamagnetic 15N and 13C resonances of Pdxo have been made using multidimensional NMR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
64
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 52 publications
1
64
0
Order By: Relevance
“…Tryptophan 106 was chosen because it has substantial conformational freedom in Pdx (16,36,37) and can occupy multiple positions at the interface in the Pdr-Pdx complex. Theoretical calculations predict that elimination of the indole ring or its reorientation could either slow down or facilitate interprotein electron transfer process (Table II).…”
Section: Rationale For the Mutation Of Specific Amino Acids Ofmentioning
confidence: 99%
“…Tryptophan 106 was chosen because it has substantial conformational freedom in Pdx (16,36,37) and can occupy multiple positions at the interface in the Pdr-Pdx complex. Theoretical calculations predict that elimination of the indole ring or its reorientation could either slow down or facilitate interprotein electron transfer process (Table II).…”
Section: Rationale For the Mutation Of Specific Amino Acids Ofmentioning
confidence: 99%
“…In hepatic P450 systems, the redox partner is the NADPH-dependent diflavin-cytochrome P450 reductase, which contains FAD and FMN cofactors (1,5). In mammalian adrenal systems and many bacterial P450 enzymes, electrons are delivered via a two-protein redox system comprising an FAD-containing reductase (adrenodoxin reductase or ferredoxin reductase) and an iron-sulfur protein (ferredoxin) (6,7). However, other forms of redox systems supporting P450 catalysis are known to exist, including the direct interaction of P450 with hydrogen peroxide to facilitate fatty acid hydroxylation in the Bacillus subtilis P450 BS␤ enzyme (8).…”
mentioning
confidence: 99%
“…The ET from NADH to P450cam is sequentially mediated by a flavin group of putidaredoxin reductase and a [2Fe-2S] center of putidaredoxin (Pdx). With the availability of the P450cam (3) and Pdx (4,5) structures, many investigators have performed the kinetic (6 -9), mutational (10 -14), and theoretical (15,16) studies to clarify the molecular mechanism for the ET reaction in the P450cam⅐Pdx system. These studies demonstrated that Pdx interacts with the proximal surface of P450cam through the electrostatic interaction (12,15,17) and suggested that Arg-112 at the putative Pdx binding site forms the ET pathway in the P450cam⅐Pdx complex (12,16).…”
mentioning
confidence: 99%
“…Low potential ironsulfur protein such as spinach ferredoxin and bovine adrenodoxin can donate an electron to ferric P450cam (the first ET) but yield no hydroxylation products. On the other hand, the addition of rat liver cytochrome b 5 (cyt b 5 ) and bacterial rubredoxins to oxy-P450cam can yield the hydroxylation product, whereas these non-physiological electron donors cannot transfer the first electron to ferric P450cam. Thus, the specific complex formation between P450cam and Pdx is required for the turnover reaction.…”
mentioning
confidence: 99%